2021
DOI: 10.1177/21925682211022311
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Spine Surgery: Global Perspectives and Practices

Abstract: Study Design: Cross-sectional, anonymous, international survey. Objectives: The COVID-19 pandemic has resulted in the rapid adoption of telemedicine in spine surgery. This study sought to determine the extent of adoption and global perspectives on telemedicine in spine surgery. Methods: All members of AO Spine International were emailed an anonymous survey covering the participant’s experiences with and perceptions of telemedicine. Descriptive statistics were used to depict responses. Responses were compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 29 publications
(53 reference statements)
0
33
0
Order By: Relevance
“…We would like to share ideas on “Telemedicine in Spine Surgery: Global Perspectives and Practices.” 1 Riew et al concluded that “ Our study noted significant geographical differences in the rate of telemedicine adoption and the platform of telemedicine utilized .” 1 We totally agree about the disequilibrium in using telemedicine for spine surgery in different areas. In our area, facilities of internet are usually limited and there are also limited number of physician who can perform spine surgery.…”
mentioning
confidence: 73%
“…We would like to share ideas on “Telemedicine in Spine Surgery: Global Perspectives and Practices.” 1 Riew et al concluded that “ Our study noted significant geographical differences in the rate of telemedicine adoption and the platform of telemedicine utilized .” 1 We totally agree about the disequilibrium in using telemedicine for spine surgery in different areas. In our area, facilities of internet are usually limited and there are also limited number of physician who can perform spine surgery.…”
mentioning
confidence: 73%
“…Use of telemedicine by spine surgeons has grown from 10% to more than 39% of all visits during the COVID-19 pandemic. 31 Some studies have shown that telemedicine visits can be as effective as in-person visits in an orthopedic patient population. 32 Although the cases of many neurosurgical patients may be more complicated and require in-person neurological examinations, postoperative telemedicine check-ins may prove to be a feasible option for routine procedures in uncomplicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50% of telemedicine users have experienced technical difficulties during at least 15% of visits. 31 When implemented correctly, however, it can be a useful adjunct to in-person visits while maintaining safety. A 2021 systematic review by Ng et al found that surgical site infections could be diagnosed via telemedicine 70% to 100% of the time compared with in-person examinations.…”
Section: Discussionmentioning
confidence: 99%
“…(25%). 1 Although telemedicine is showing to provide convenient and safety health care to patients during COVID-19 pandemic, there is still much uncertainty as to whether it will have a permanent role in treating spine patients. 3 Although telemedicine is a new and rapidly evolving field, it is important to pay attention to potential malpractice litigation in telemedicine that could occur, as misdiagnoses or failure to identify pressing issues at home may create legal implications.…”
mentioning
confidence: 99%